Colombia - Financial Sector Assessment - IMF; World Bank (World Bank, Washington, DC, 2022)
State-owned financial institutions (SOFIs) and broader interventions by the state need to play a more prominent role in supporting financial inclusion, green activities and fostering competition among private financial providers. While SOFIs have been generally perceived as complementary to the private sector, their recent incursion into direct lending and commercial activities could raise competitive neutrality considerations, if subsidies are involved. Improving product design, incorporating best practices, strengthening governance, and continuing to improve risk management would support expansion of SOFIs activities in a non-distortionary way. Interventions could be better coordinated to improve efficiency, avoid duplication, and ensure alignment with policy objectives. The formalization of Grupo Bicentenario should contribute to these objectives. Monitoring and evaluation (M&E) of public credit support policies and programs could be strengthened. Finally, interest rate controls and mandatory investment requirements to fund the agricultural sector should be reviewed to limit distortions. Colombia has a well-developed market for NPL management, while the insolvency framework is in a stage of transition and with areas for improvement. Strong and efficient NPL resolution and insolvency frameworks are key for financial sector stability and development. There is an active and competitive market for sales of written-off loans, mainly in unsecured segments, with an extensive availability of investors and market infrastructure. Active resolution of NPLs should continue to be encouraged by the SFC, particularly for commercial NPLs, for which NPL management by third-party providers is scarce. Several recent regulations related to the insolvency framework have been introduced, including temporary emergency decrees that make considerable modifications to the corporate insolvency system. This transitory situation creates uncertainty in the users of the insolvency system, in particular large corporations, and creditors. The incorporation of some of the provisions from these temporary decrees into the bankruptcy law would be advisable. The ultimate judge of corporate insolvency is an administrative entity (the Superintendency of Companies) which is specialized and enjoys good reputation, but the rotation of its authorities and the executive’s capacity to remove them poses severe challenges for the predictability of its criteria. Finally, the personal insolvency system requires urgent attention.